A streamlined cloning workflow minimising the time-to-strain pipeline for Pichia pastoris - Royle,KE; Polizzi,KM (Scientific Reports, 2017)
Although recent advances in E. coli self-assembly have greatly simplified cloning, these have not yet been harnessed for the high-throughput generation of expression strains in the early research and discovery phases of biopharmaceutical production. Here, we have refined the technique and incorporated it into a streamlined workflow for the generation of Pichia pastoris expression strains, reducing the timeline by a third and removing the reliance on DNA editing enzymes, which often require troubleshooting and increase costs. We have validated the workflow by cloning 24 human proteins of biopharmaceutical value, either as direct therapeutics or as research targets, which span a continuous range in size and GC content. This includes demonstrating the applicability of the workflow to three-part assemblies for a monoclonal antibody and its single-chain antibody fragments derivatives. This workflow should enable future research into recombinant protein production by P. pastoris and a synthetic biology approach to this industrial host.